The Effect of Sunkist Orange (Citrus Sinensis (L.) Osbeck) Granule Extract on Ovarian Follicle Histomorphology in Female Rats (Rattus Norvegicus) with Obesity - Mutia, Maya Sari; Faridahanum, Faridahanum; Silitonga, Impola Dinita Felicia; Ramadhini, Amelya Putri; Sari, Ajeng Mestika; Lubis, Yolanda Eliza Putri; Sihotang, Widya Yanti (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Obesity is a medical condition in which a person experiences abnormal fat accumulation that exceeds normal limits, which can have a negative impact on health. Obesity sufferers are increasing, especially in developed and developing countries. The prevalence of obesity is estimated to be 42% in 2030. Risk factors that can cause obesity include unhealthy lifestyles and lack of physical activity. When there is excess fat accumulation in the body, there will be an increase in leptin levels in the body resulting in oxidative stress that triggers the emergence of free radicals that can inhibit the growth of follicles in the ovaries. To neutralize free radicals in the body, antioxidants are needed. One type of fruit that is rich in antioxidants is sunkist oranges (Citrus sinensis (L) Osbeck), this study discusses the effect of giving sunkist orange granule extract (Citrus sinensis (L) Osbeck) on the morphology of ovarian follicles in obese female wistar rats (Ratus norvegicus). Using a laboratory experimental research design with a post-test only control group design, using 25 female rats divided into 5 groups, namely the Negative Control Group, the Positive Control Group (Alloxan and High Fat), and the Treatment Group given alloxan and Sunkist orange granule extract at a dose of 50 mg / kgBW / day, 100 mg / kgBW / day, 150 mg / kgBW / day. Results: Sunkist Orange Granule Extract (Citrus sinensis (L.) Osbeck) has a significant effect on the histomorphology of ovarian follicles with obesity induction in female rats (Rattus norvegicus).